The Green Economy Perspective of Batu City: Calculating Depletion in the Tourism Sector - Hasyim Ibnu Abbas, Muhammad; Sumarsono, Hadi; Rahmawati, Farida; Nuraini Dwiputri, Inayati (KnE Social Sciences, 2021)
The concept of sustainable development has begun to be developed, namely in line with current needs and without endangering future generations. In addition to focusing on environmental issues, this concept covers economic development, environmental protection and social development. However, this concept still tends to focus on short- term economic development. With the limitation of the State Revenue and Expenditure Budget (APBN) and the resources we have, it is not surprising that policymakers prefer shortcuts. As a result, the quality of economic growth has deteriorated. One of the efforts to harmonize the needs of economic growth and conservation of natural resources is the concept of a Green Economy. This article discusses how to calculate economic development as seen from the amount of Gross Domestic Product (GDP) from a Green Economy perspective. Batu City, as a tourism city that relies on natural conditions and its environment, needs to analyze its economic development from a Green Economy perspective in order to be sustainable. This article aimed to analyze the depletion of natural resources of the sub-sector “Provision of Accommodation and Food – Beverage” which supports tourism in Batu City. The results showed that in 2015-2019, natural resource depletion increased every year. Keywords: Sustainable Development, Green Economy, Depletion, Natural Resources